Intrusions of violence: Afro-pessimism and reading social death beyond solitary confinement - Chavez, Ernest K. (Theoretical criminology, 2021)
Any serious engagement with the theory of social death must contend with Afro-pessimism. Socio-Legal Studies advances social death as an un-raced and universalizable phenomenon. Lisa Guenther’s Solitary Confinement, is exemplary of this kind of work. In order to construct a phenomenology of race, Guenther attempts to analogize a theory of slavery (social death) with a theory of phenomenology and solitary confinement. Furthermore, Guenther takes up a humanistic reading of Frantz Fanon’s work, as if Fanon was affirming the possibility of a “new humanism” that could restore social life against social death in the post-colonial wake. This essay is an attempt to provide an Afro-pessimist reading of social death; one that engages anti-blackness as a fundamental condition of civil society and provides a close reading of Fanon’s psychopolitics of racial violence.